STRATEGI KEPALA MADRASAH DALAM MEMBANGUN BUDAYA LITERASI MENULIS - Sa’adah, Halimatus (re-JIEM (Research Journal of Islamic Education Management), 2022)
Literacy culture is a culture in educational institutions considering the demands of the current era of globalization, students are required to be creative and innovative by producing many works, including the strategy of the head of the madrasa in cultivating writing. This research was conducted at the Islamic Senior High School Sumber Bungur Pakong Pamekasan. This research includes a qualitative approach with a case study type. The research results show that. First, the strategy built by the head of the madrasa in building a literacy culture consists of goals, objectives, stages, and time for planning. Second, the implementation of school principals in building a literacy culture, namely formulating a collaboration, fulfilling facilities, providing motivation, and preparing bulletin boards. The supporting and inhibiting factors for the madrasa head in building a literacy culture are all supporting facilities, competent teachers, and financing management. The inhibiting factor for literacy is that it is necessary to be continuously motivated in order to produce a quality literacy culture.